MODEL OF GAWAI DAYAK BASED-SOCIAL CAPITAL IN THE BORDER OF SAJINGAN BESAR OF WEST KALIMANTAN - Herlan Herlan; Elyta Elyta (Universitas Padjadjaran, 2020)
The ceremony of gawai Dayak has its own uniqueness in each region. Particularly in the region of Sajingan Besar, the Indonesia-Malaysia border, Gawai Dayak forms a unique social capital and locality. Thus the purpose of this study is to design a social capital model based on Gawai Dayak at the border of Sajingan Besar, West Kalimantan. This research uses the action research method approach with the Fast and Participatory Assessment model. Participants came from informants local government, Non-Goverment (NGOs), community leaders in the form of in-depth interviews. The findings of this study are the existence of unique social capital in Gawai Dayak rituals in the people of Sajingan Besar. Based on the results of this study indicate that Gawai Dayak is a unique social capital that is reconstructed in Gawai rituals, namely the ba’aek and ba’komok traditions. The ba’aek and ba’komo” traditions are rituals in the ceremony of Gawai Dayak. Social capital is formed through local institutions such as mutual cooperation and mutual trust between communities, then the Gawai Dayak becomes a bond of friendship, cooperation, togetherness, mutual care between individuals and the community, and it can be converted into political capital that is political participation which then becomes political participation becomes unique local norms and values. Based on the results of the study, it can be concluded that the social capital contained in the Gawai Dayak is seen in the Ba’aek and Ba’komo rituals. In both of these rituals, a unique locality is found and is only found in the Dayak community in Sajingan Besar.